Effects of fiber orientation on the frictional properties and damage of regenerative articular cartilage surfaces - Accardi,MA; McCullen,SD; Callanan,A; Chung,S; Cann,PM; Stevens,MM; Dini,D (Tissue Engineering: Parts A, B, and C, 2013)
Articular cartilage provides a low-friction, wear-resistant surface for diarthrodial joints. Due to overloading and overuse, articular cartilage is known to undergo significant wear and degeneration potentially resulting in osteoarthritis (OA). Regenerative medicine strategies offer a promising solution for the treatment of articular cartilage defects and potentially localized early OA. Such strategies rely on the development of materials to restore some aspects of cartilage. In this study, microfibrous poly(-caprolactone) scaffolds of varying fiber orientations (random and aligned) were cultured with bovine chondrocytes for 4 weeks in vitro, and the mechanical and frictional properties were evaluated. Mechanical properties were quantified using unconfined compression and tensile testing techniques. Frictional properties were investigated at physiological compressive strains occurring in native articular cartilage. Scaffolds were sheared along the fiber direction, perpendicular to the fiber direction and in random orientation. The evolution of damage as a result of shear was evaluated via white light interferometry and scanning electron microscopy. As expected, the fiber orientation strongly affected the tensile properties as well as the compressive modulus of the scaffolds. Fiber orientation did not significantly affect the equilibrium frictional coefficient, but it was, however, a key factor in dictating the evolution of surface damage on the surface. Scaffolds shear tested perpendicular to the fiber orientation displayed the highest surface damage. Our results suggest that the fiber orientation of the scaffold implanted in the joint could strongly affect its resistance to damage due to shear. Scaffold fiber orientation should thus be carefully considered when using microfibrous scaffolds.